2020
DOI: 10.1007/s11249-020-01344-3
|View full text |Cite
|
Sign up to set email alerts
|

Surface Gel Layers Reduce Shear Stress and Damage of Corneal Epithelial Cells

Abstract: Soft contact lenses are medical devices made from aqueous polymeric gels that are worn on the eye to correct refractive errors. These devices interrupt the natural contact pairing between the cornea and the eyelid and create two interfaces comprised of a synthetic material and the epithelia-contact lens surfaces versus (1) the cornea and (2) the eyelid conjunctiva. The cellular responses to friction and shear stress are thought to contribute to contact lens discomfort. This study performs direct contact shear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…Moreover, creating a lens with a slippery front side and comparatively higher friction on the reverse side could, for example, help keeping the lens position during a blink of the eye. Since the method enables surfaces to be created with small differences in friction, the friction values on both sides of the lens could be kept low enough to avoid applying excessive shear to the corneal epithelium [35,36].…”
Section: Spatial Control Of Frictionmentioning
confidence: 99%
“…Moreover, creating a lens with a slippery front side and comparatively higher friction on the reverse side could, for example, help keeping the lens position during a blink of the eye. Since the method enables surfaces to be created with small differences in friction, the friction values on both sides of the lens could be kept low enough to avoid applying excessive shear to the corneal epithelium [35,36].…”
Section: Spatial Control Of Frictionmentioning
confidence: 99%
“…Several studies have measured the friction of CLs. 6,7,16,17 We recently developed a pendulum-type friction tester for CLs, which is a modification of a friction tester for artificial joints. 18 In the current study, we measured the friction of a commercially available silicone hydrogel SCL using a range of HA concentrations to evaluate the effect of its lubrication property using the newly modified pendulum-type friction tester.…”
mentioning
confidence: 99%
“…40 However, the coefficient of friction between the conventional silicone hydrogel contact lens and the cornea is reported to be in the range from 0.04 to 0.08. 41 As the coefficient of friction of human corneal tissue is reported to be 0.015 ± 0.09 in a tear-like fluid in phosphatebuffered saline, 42 it is clear that the PMPC-modified silicone hydrogel contact lens possesses a sufficiently low coefficient of friction against the cornea tissue.…”
Section: Resultsmentioning
confidence: 99%
“…The lubrication mechanism on the PMPC-modified surface has also been analyzed, and it has been shown that the hydrated PMPC layer provides fluid lubrication. , The coefficient of friction when sliding between the hydrogel and the human cornea is 0.03 . However, the coefficient of friction between the conventional silicone hydrogel contact lens and the cornea is reported to be in the range from 0.04 to 0.08 . As the coefficient of friction of human corneal tissue is reported to be 0.015 ± 0.09 in a tear-like fluid in phosphate-buffered saline, it is clear that the PMPC-modified silicone hydrogel contact lens possesses a sufficiently low coefficient of friction against the cornea tissue.…”
Section: Resultsmentioning
confidence: 99%